Developing and validating a HEalthCare NAvigation Competency (HECNAC) Scale for refugees in the United States. - Sarah Yeo; Inseok Lee; John Ehiri; Priscilla Magrath; Kacey Ernst; Yu Ri Kim; Halimatou Alaofè (PLoS ONE)
The complex healthcare system in the United States (US) poses significant challenges for people, particularly minorities such as refugees. Refugees often encounter additional layers of challenges to healthcare navigation due to unfamiliarity with the system, limited health literacy, and language barriers. Despite their challenges, it is difficult to identify the gaps as few tools exist to measure navigation competency among this population and many conventional tools assume English proficiency, making them inadequate for refugees and other immigrants. To address this gap, this study developed and validated a HEalthCare NAvigation Competency (HECNAC) Scale tailored to refugees' needs. The scale development process followed three phases: domain identification through a literature review and stakeholder interviews (n = 15), content validation through the Delphi method (2 rounds, n = 12), and face validity assessment via cognitive interviews (2 rounds, n = 4). Based on a literature review and stakeholder interviews, the initial version of the scale was developed, including ten domains and 47 items. An introductory email concerning the scale and the Delphi process was subsequently sent to 21 eligible experts, including staff from refugee resettlement agencies, health care providers serving refugee communities, and refugees. Twelve experts completed the two rounds of the Delphi, resulting in a consensus on 39 items. After conducting cognitive interviews with 4 Afghan refugees, the scale was finalized with ten domains and 35 items. The finalized scale captures multifaceted aspects of healthcare navigation crucial for refugees, organized into domains such as health system knowledge, insurance, making an appointment, transportation, preparing for a visit, in the clinic, interpretation, medicine, medical bills, and preventive care. Overall, the HECNAC Scale represents a significant step towards understanding and assessing refugees' competencies in navigating the US healthcare system. It has the potential to guide tailored interventions and standardized training curricula and ultimately mitigate persistent barriers faced by refugees in accessing healthcare services.